SYNERGISTIC EFFECTS OF BIOCHAR AND MICROBIAL INOCULANTS ON DROUGHT TOLERANCE AND WATER-USE EFFICIENCY IN MAIZE (Zea mays L.) - Samanhudi; Lixin Zhang; Hassan Bashir; Muji Rahayu; Andriyana Setiyawati; Iswahyudi (UIN Sunan Gunung Djati Bandung, 2026)
Drought is a primary constraint to global maize (Zea mays L.) production, and both biochar amendments and bacterial plant growth-promoting rhizobacteria (PGPR) have shown potential to mitigate its effects. However, no maize-specific meta-analysis has quantified whether these interventions act synergistically. Following PRISMA 2020 guidelines, we searched Scopus and Web of Science, identified 1,270 records, and after systematic screening selected 148 studies (52 biochar-only, 55 bacteria-only, 41 combined) from 28 countries (2009-2026). Preliminary random-effects meta-analysis of 87 effect sizes from 16 studies with complete variance data showed that amendments significantly improved multiple drought tolerance indicators. Bacterial inoculation increased measured outcomes by 26.8% (95% CI: 15.8-38.8%, p < 0.001), while biochar improved them by 5.4% (95% CI: 3.1-7.8%, p < 0.001). Significant improvements were detected for chlorophyll content (+58.8%), root length (+31.4%), relative water content (+20.3%), shoot dry weight (+16.8%), and photosynthetic rate (+14.2%). Substantial heterogeneity (I2 = 78-100%) across most outcomes indicates strong moderation by experimental conditions. These findings directly contribute to Sustainable Development Goal 2 (Zero Hunger) and SDG 13 (Climate Action), SDG 6 (Clean Water and Sanitation), SDG 12 (Responsible Consumption and Production), and SDG 8 (Decent Work and Economic Growth). This study provides a comprehensive framework and preliminary quantitative evidence supporting the use of integrated biochar-bacteria strategies for drought-resilient maize production, with full results forthcoming upon completion of data extraction from all 148 studies.